2013
DOI: 10.18511/0103-1716/rbcm.v21n2p123-134
|View full text |Cite
|
Sign up to set email alerts
|

Autopercepção de Competência Pedagógica de Professores de Educação Física no Ensino Inclusivo

Abstract: O objetivo deste estudo foi analisar a Autopercepção de competência pedagógica de 33 professores, da rede municipal de ensino de Florianópolis, frente ao ensino inclusivo nas aulas de Educação Física regular. Utilizou-se, como instrumento, um questionário composto por 46 questões, para obter dados biográficos e da Autopercepção de competência profissional em Educação Física. Os dados foram tratados com estatística descritiva e inferencial, teste "t" de Student e Qui-quadrado. Verificou-se que os professores pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
0
3
0
10
Order By: Relevance
“…We have presented here an evolution in the concept of inclusion, revealing a positive advance compared to previous Brazilian studies with physical education teachers (AGUIAR; DUARTE, 2005;FALKENBACH et al, 2007;FIORINI, MANZINI, 2014;MUNSTER, 2013;RAMOS et al, 2013;RODRIGUEZ, FERREIRA, 2013). The participants of this study recognized the need to adapt classes not only due to the presence of students with disability, but also for other students, such as those with obesity or behavioral disorders, or even for those who are shy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We have presented here an evolution in the concept of inclusion, revealing a positive advance compared to previous Brazilian studies with physical education teachers (AGUIAR; DUARTE, 2005;FALKENBACH et al, 2007;FIORINI, MANZINI, 2014;MUNSTER, 2013;RAMOS et al, 2013;RODRIGUEZ, FERREIRA, 2013). The participants of this study recognized the need to adapt classes not only due to the presence of students with disability, but also for other students, such as those with obesity or behavioral disorders, or even for those who are shy.…”
Section: Discussionmentioning
confidence: 51%
“…Studies conducted in the Brazilian educational context revealed that physical education teachers were unaware of what may be modified in educational programs to meet students needs (AGUIAR; DUARTE, 2005;FALKENBACH et al, 2007;FIORINI, MANZINI, 2014;MUNSTER, 2013;RAMOS et al, 2013;RODRIGUEZ, FERREIRA, 2013). Among Brazilian physical education teachers, there was no consensus related to the inclusion of all children in regular schools, as many felt that students with more severe disability should be educated in special schools (FRANK et al, 2013;FALKENBACH et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…No tocante aos professores de educação física (PEF), estudos realizados na área revelam ainda dificuldades no processo formativo, com um sentimento de despreparo para atendimento do aluno com deficiência (GORGATTI; ROSE JÚNIOR, 2009;FALKENBACH;LOPES, 2010;RAMOS et al, 2013;FIORINI;MANZINI, 2014;ALVES et al, 2017;GREGUOL et al, 2018). O processo de formação destes PEF é descrito como insuficiente e sem relação com a realidade escolar.…”
Section: Introductionunclassified
“…Studies in the Brazilian educational context reveal that PE teachers are not aware of what can and cannot be modified in the educational programs to meet the needs of students with disabilities (Aguiar & Duarte, 2005;Falkenbach, Chaves, Nunes, & Nascimento, 2007;Falkenbach & Lopes, 2010;Ferreira, 2006;Fiorini & Manzini, 2014;Munster, 2013;Ramos, Brasil, Goda, Barros, & Both, 2013). In addition, Brazilian schools still have PE teachers with no training in inclusion (Ramos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%